2020
DOI: 10.1152/physiol.00024.2019
|View full text |Cite
|
Sign up to set email alerts
|

Breast Biomechanics: What Do We Really Know?

Abstract: Although half the world’s population will develop breasts, there is limited research documenting breast structure or motion. Understanding breast structure and motion, however, is imperative for numerous applications, such as breast reconstruction, breast modeling to better diagnose and treat breast pathologies, and designing effective sports bras. To be impactful, future breast biomechanics research needs to fill gaps in our knowledge, particularly related to breast composition and density, and to improve met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 158 publications
0
23
0
Order By: Relevance
“…Running is a popular form of physical activity that has been shown to benefit cardiovascular and musculoskeletal health (Williams et al, 1984 ; Piacentini et al, 2013 ; Lavie et al, 2015 ; Kozlovskaia et al, 2019 ). For many women, however, breast pain is a significant barrier to exercise including running-based activities (Scurr et al, 2011a ; Risius et al, 2017 ; Brisbine et al, 2020 ; McGhee and Steele, 2020b ). It is reported that up to 72% of females experience breast pain during exercise-related activities (Gehlsen and Albohm, 1980 ; Bowles et al, 2008 ; Scurr et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Running is a popular form of physical activity that has been shown to benefit cardiovascular and musculoskeletal health (Williams et al, 1984 ; Piacentini et al, 2013 ; Lavie et al, 2015 ; Kozlovskaia et al, 2019 ). For many women, however, breast pain is a significant barrier to exercise including running-based activities (Scurr et al, 2011a ; Risius et al, 2017 ; Brisbine et al, 2020 ; McGhee and Steele, 2020b ). It is reported that up to 72% of females experience breast pain during exercise-related activities (Gehlsen and Albohm, 1980 ; Bowles et al, 2008 ; Scurr et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the range of breast projection distances documented in the current study (23–71 mm), women with breasts that protrude further anteriorly from the chest wall are likely to experience greater difficulty achieving conformity between a body armour system and their torso (Coltman et al, 2021b ). The resultant compression and deformation of the breast when wearing body armour, which is exaggerated in women with large breasts (McGhee and Steele, 2020 ), is likely to have negative functional and protection impacts (e.g., difficulty breathing, limited ROM, exposed lateral breast tissue, and compromised positioning of vital torso protection). Consequently, our findings corroborate previous reports that occupational body armour does not adequately accommodate the full range of female breast characteristics (Coltman et al, 2020 , 2021a ; Malbon et al, 2020 ; Niemczyk et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A correctly fitting bra can reduce exercise-related breast pain, avoid deep furrows due to strap pressure, and reduce the risk for neck and back pain [ 35 ]. Exercise-induced breast pain is thought to be the result of the breasts hitting the torso when a woman’s foot strikes the ground when she runs [ 36 ]. When women wear more supportive bras, they experience less breast motion and less exercise-induced breast pain.…”
Section: Optimizing Performance For Female Athletesmentioning
confidence: 99%